Dietary flavonoid and lignan intake and breast cancer risk according to menopause and hormone receptor status in the European Prospective Investigation into Cancer and Nutrition (EPIC) Study. - Zamora-Ros, R; Ferrari, P; González, C; Tjønneland, A; Olsen, A; Bredsdorff, L; Overvad, K; Touillaud, M; Perquier, F; Fagherazzi, G; Lukanova, A; Tikk, K; et al. (2013)
Evidence on the association between dietary flavonoids and lignans and breast cancer (BC) risk is inconclusive, with the possible exception of isoflavones in Asian countries. Therefore, we investigated prospectively dietary total and subclasses of flavonoid and lignan intake and BC risk according to menopause and hormonal receptor status in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. The study included 334,850 women, mostly aged between 35 and 70 years from ten European countries. At baseline, country-specific validated dietary questionnaires were used. A flavonoid and lignan food composition database was developed from the US Department of Agriculture, the Phenol-Explorer and the UK Food Standards Agency databases. Cox regression models were used to analyse the association between dietary flavonoid/lignan intake and the risk of developing BC. During an average 11.5-year follow-up, 11,576 incident BC cases were identified. No association was observed between the intake of total flavonoids [hazard ratio comparing fifth to first quintile (HRQ5-Q1) 0.97, 95 % confidence interval (CI): 0.90-1.04; P trend = 0.591], isoflavones (HRQ5-Q1 1.00, 95 % CI: 0.91-1.10; P trend = 0.734), or total lignans (HRQ5-Q1 1.02, 95 % CI: 0.93-1.11; P trend = 0.469) and overall BC risk. The stratification of the results by menopausal status at recruitment or the differentiation of BC cases according to oestrogen and progesterone receptors did not affect the results. This study shows no associations between flavonoid and lignan intake and BC risk, overall or after taking into account menopausal status and BC hormone receptors.